Preconceptional brain structure and future conception: a prospective brain MRI study among 321 women - Merel W. de Vries; Eline M. P. Poels; Gennady V. Roshchupkin; Ryan L. Muetzel; Milan Zarchev; Astrid M. Kamperman; Henning Tiemeier; Meike W. Vernooij; Steven A. Kushner (Scientific Reports)
Abstract Brain structure may influence female fertility through its reciprocal relationship with the endocrine system, but this hypothesis is underexplored. This study investigated the association between preconceptional brain structure and the likelihood of conception in a prospective population-based neuroimaging cohort. Women intending to conceive within a year were recruited and structural brain MRI scans were collected from 321 participants between June 2019 and March 2021. During the 12-month follow-up, 185 women became pregnant, and 136 did not. Logistic regression was used to examine associations between global brain parameters and conception, adjusting for age, intracranial volume, BMI, prior STD diagnosis, ethnicity, education, household income, smoking, and alcohol use. Unadjusted analyses showed associations between conception and larger occipital lobe and nucleus accumbens volume, increased surface area across all lobes, and occipital cortical thickness, and conception. Adjusted analyses identified a positive association between nucleus accumbens volume and conception (OR = 1.50 (95% CI: 1.12, 1.99), p-value = 0.007). Sensitivity analyses linked caudate volume to conception, but no findings remained significant after correction for multiple comparisons. Further research is needed to understand the potential role of brain structure and function in conception, in relationship with general health and socioeconomic factors.